Angiotensin II Receptor Blockers and Cancer Risk: A Meta-Analysis of Randomized Controlled Trials. Issue 18 (May 2016) - Zhao, Yun-Tao; Li, Peng-Yang; Zhang, Jian-Qiang; Wang, Lei; Yi, Zhong
Abstract : Abstract: Angiotensin II receptor blockers (ARB) are widely used drugs that are proven to reduce cardiovascular disease events; however, several recent meta-analyses yielded conflicting conclusions regarding the relationship between ARB and cancer incidence, especially when ARB are combined with angiotensin-converting enzyme inhibitors (ACEI). We investigated the risk of cancer associated with ARB at different background ACEI levels. Search of PubMed and EMBASE (1966 to December 17, 2015) without language restriction. Randomized, controlled trials (RCTs) had at least 12 months of follow-up data and reported cancer incidence was included. Study characteristics, quality, and risk of bias were assessed by 2 reviewers independently. Nineteen RCTs including 148, 334 patients were included in this study. Random-effects model meta-analyses were used to estimate the risk ratio (RR) of cancer risk. No excessive cancer risk was observed in our analyses of ARB alone versus placebo alone without background ACEI use (risk ratio [RR] 1.08, 95% confidence interval [CI] 1.00–1.18, P  = 0.05); ARB alone versus ACEI alone (RR 1.03, 95%CI 0.94–1.14, P  = 0.50); ARB plus partial use of ACEI versus placebo plus partial use of ACEI (RR 0.97, 95%CI 0.90–1.04, P  = 0.33); and ARB plus ACEI versus ACEI (RR 0.99, 95%CI 0.79–1.24, P  = 0.95). Lack of long-term data, inadequate reporting of safety data, significant heterogeneity in underlying study populations, and treatment regimens. ARB have a neutral effect on cancer incidence in randomized trials. We observed no significant differences in cancer incidence when we compared ARB alone with placebo alone, ARB alone with ACEI alone, ARB plus partial use of ACEI with placebo plus partial use of ACEI, or ARB plus ACEI combination with ACEI.